How Does Angel Investor–Entrepreneur Conflict Affect Venture Innovation? It Depends. (May 2016) - Collewaert, Veroniek; Sapienza, Harry J.
This study examines how angel investor–entrepreneur task conflicts are related to portfolio company innovativeness and how this relationship is moderated by the level of agreement on priorities, diversity of entrepreneurial experience, and the level of communication. Using survey data gathered from 54 teams of angels and entrepreneurs in Belgium and the United States, we show that the negative relationship between task conflict and innovativeness is more severe when the teams have lower levels of agreement on priorities, when there is less diversity of experience in the team, and when the teams communicate more frequently.